Charles Stoers Hamilton, Charter and Ordinances of the City of New Haven, Together with Legislative Acts Affecting Said City 164 (1890) - (:unkn) unknown (My University, 1890)
§ 192: Prohibited the concealed carrying of any metal knuckles, pistol, slungshot, stiletto, or similar weapons, absent written permission of the mayor or superintendent of police. Punishable by a fine of $5-50.
Keywords: CARRY - CONCEALED